Facile and large‐scale production of Ag nanoparticles for selective electrochemical CO2 reduction reaction. (14th September 2021) - Abbas, Syed Asad; Ma, Ahyeon; Seo, Dongho; Lim, Yun Ji; Park, Joon Yong; Lee, Gaehang; Nam, Ki Min
Abstract: Electrochemical CO2 reduction to carbon monoxide (CO) is immensely important for sustainable CO2 recycling. In this study, we established a facile synthetic method for large‐scale production of Ag nanoparticles, which can be used for the selective electrochemical reduction of CO2 to CO. Thermal decomposition and reduction of AgNO3 produced Ag nanoparticles on a gram‐scale in high yield (over 90%) with a homogeneous size distribution. The oleylamine‐capped Ag nanoparticles were quasi‐spherical with diameters of 9 ± 2 nm. Ag nanoparticles are capable of electrochemical CO2 reduction to CO with high activity and stability. The CO selectivity of the catalyst was in the vicinity of 90% over a wide potential range and reached 94.2% at −1.4 V vs. RHE. The Ag nanoparticles showed good stability over 24 h. Different surface functional groups, for example, thiol and citrate were investigated to understand their influence on the variation in CO selectivity. Abstract : Thermal decomposition and reduction of AgNO3 in oleylamine produced amine‐functionalized Ag nanoparticles (Ag‐NPs‐Amine) with a homogeneous size distribution. The nanoparticles were quasi‐spherical with diameters of 9 ± 2 nm. The Ag‐NPs‐Amine as a cathode was capable of electrochemical CO2 reduction to CO with high selectivity and stability.